Implementation of Bloom's Taxonomy in the preparation of Islamic Religious Education Learning Evaluations - Khansya Asyafa, Mila; Naofal, Ahmad; Nugraha, Enung (The Future of Education Journal, 2025)
The implementation of Bloom's Taxonomy in Islamic Religious Education (PAI) learning evaluation provides educators with guidelines for developing systematic evaluation instruments that are appropriate to students' cognitive and attitudinal development levels, resulting in more accurate and comprehensive evaluation results. This study aims to determine how Bloom's Taxonomy is used to develop PAI learning evaluations. This study employed a qualitative approach with a literature review method. This method was chosen to study and analyze various theories and literature from various sources relevant to the research topic. This study confirms that implementing Bloom's Taxonomy in developing PAI learning evaluations is essential to address evaluation constraints, which have historically been limited to lower cognitive aspects. The results indicate that implementing Bloom's Taxonomy-based evaluations helps teachers develop questions, assignments, and learning activities more systematically and in accordance with established objectives. This encourages the development of higher-order thinking skills (HOTS) in students. Thus, the use of Bloom's Taxonomy helps teachers holistically assess student abilities, formulate learning objectives, and design more effective learning activities, ultimately contributing to improved student cognitive abilities.